Clinical and virological course of SARS-CoV 2 infected patients in a tertiary care hospital in Pakistan - Hussain, Ashfaq; Satti, Luqman; Hanif, Faisal; Shoaib, Muhammad; Ghauri, Muhammad Asim; Niazi, Ghulam Abbas Khan; Khan, Muhammad Nadir; Sana, Fatima; Yunus, Faryal (Journal of Ayub Medical College Abbottabad, 2021)
Background: Acute respiratory illness caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) involved the whole globe within no time. Various studies published globally have shown variable severity of disease and mortality. The objective of our study was to describe clinical and epidemiological characteristics of the disease in our setup. Methods: in this descriptive case series, individuals with signs and symptoms of Coronavirus disease-19 (COVID-19) and asymptomatic patients with history of close contact to confirmed COVID-19 patients were considered for SARS-CoV-2 Polymerase chain reaction (PCR) assay. Epidemiological and clinical features of only PCR positive cases were recorded. Data regarding hospitalization status, exposure to known COVID-19 patients, clinical feature and clinical outcome of patients was collected and interpreted. Results: A total of 266 patients were found to be SARS-CoV 2 PCR positive which were included in the study. Mean age of patients was 39.45±31.9 years and majority of the patients in our study were male, i.e., 238 (89.5%). Most common clinical features among COVID-19 symptomatic patients were fever and dry cough followed by myalgias and sore throat. Eighteen (7%) out of 266 died in our setup. Time duration of viral shedding after initial positive PCR varied between 11 days to up to more than 55 days. Conclusions: Coronavirus disease-19 (COVID-19) can present with wide range of clinical spectrum and disease can be life threatening. Severity of disease, requirement of ICU care and mortality were directly related to age of the patient and underlying comorbidities. Rigorous precautionary measures are of utmost importance particularly in this high-risk population.